Barriers to influenza vaccination of children hospitalised for acute respiratory illness: A cross‐sectional survey. (22nd October 2020) - Carlson, Samantha J; Quinn, Helen E; Blyth, Christopher C; Cheng, Allen; Clark, Julia; Francis, Joshua R; Marshall, Helen S; Macartney, Kristine; Leask, Julie
Abstract : Aim: To identify barriers to influenza vaccination of children hospitalised for acute respiratory illness in Australia. Methods: A total of 595 parents of children hospitalised with acute respiratory illness across five tertiary hospitals in 2019 participated in an online survey. Multivariate logistic regression identified factors most strongly associated with influenza vaccination barriers. Results: Odds of influenza vaccination were lower with lack of health‐care provider (HCP) recommendation (adjusted odds ratio (aOR) 0.18; 95% confidence interval (CI): 0.08–0.38); if parents had difficulties (aOR 0.19; 95% CI: 0.08–0.47) or were 'neutral' (aOR 0.23; 95% CI: 0.06–0.82) in remembering to make an appointment; and if parents had difficulties (aOR 0.21; 95% CI: 0.07–0.62) or were 'neutral' (aOR 0.24; 95% CI: 0.07–0.79) regarding getting an appointment for vaccination. Odds were also lower if parents did not believe (aOR 0.27; 95% CI: 0.08–0.90) or were 'neutral' (aOR 0.15; 95% CI: 0.04–0.49) regarding whether the people most important to them would have their child/ren vaccinated against influenza. Children had lower odds of vaccination if parents did not support (aOR 0.09; 95% CI: 0.01–0.82) or were ambivalent (aOR 0.09; 95% CI: 0.01–0.56) in their support for influenza vaccination. Finally, lack of history of influenza vaccination of child (aOR 0.38; 95% CI: 0.18–0.81) and respondent (aOR 0.25; 95% CI: 0.11–0.56) were associated with lack of receipt of influenza vaccine before admission for acute respiratory infection. Conclusions: Assisting parents in remembering and accessing influenza vaccination and encouraging health‐care providers to recommend vaccination may increase uptake.